2019
DOI: 10.1175/jas-d-18-0290.1
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Trailing Gravity Waves from New Zealand

Abstract: Gravity waves are frequently observed in the stratosphere, trailing long distances from mid- to high-latitude topography. Two such trailing-wave events documented over New Zealand are examined using observations, numerical simulations, and ray-tracing analysis to explore and document stratospheric trailing-wave characteristics and formation mechanisms. We find that the trailing waves over New Zealand are orographically generated and regulated by several processes, including interaction between terrain and moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…The long-lasting flow over Greenland excited inertia-gravity waves with horizontally long modes (λ > 500 km) propagating into the direction of the ambient wind, a process similar to that observed in the lee of the Scandinavian mountains (Dörnbrack et al, 1999(Dörnbrack et al, , 2002. The additional meridional propagation into the PNJ is a dynamical process well-described by Sato et al (2012) and further discussed by Ehard et al (2017) and Jiang et al (2019) for the Southern Hemisphere. Figure 4 displays vertical sections along the baseline sketched in Figure 3 for the 25 January 2005 18 UTC (i.e., 24 hr before our q H2O observation) and 26 January 2005 18 UTC.…”
Section: Numerical Weather Prediction Model Datamentioning
confidence: 62%
“…The long-lasting flow over Greenland excited inertia-gravity waves with horizontally long modes (λ > 500 km) propagating into the direction of the ambient wind, a process similar to that observed in the lee of the Scandinavian mountains (Dörnbrack et al, 1999(Dörnbrack et al, , 2002. The additional meridional propagation into the PNJ is a dynamical process well-described by Sato et al (2012) and further discussed by Ehard et al (2017) and Jiang et al (2019) for the Southern Hemisphere. Figure 4 displays vertical sections along the baseline sketched in Figure 3 for the 25 January 2005 18 UTC (i.e., 24 hr before our q H2O observation) and 26 January 2005 18 UTC.…”
Section: Numerical Weather Prediction Model Datamentioning
confidence: 62%
“…This step drastically reduces the number of mesh points required near the surface thus allowing us to cluster the bulk of the points at the upper altitudes where instability and wave breaking occur. From a GW perspective, the main effect of the boundary layer is an adjustment of the effective terrain shape due to its displacement effect, and perhaps local regions of separated flow behind steep leeward ridges (e.g., Jiang et al 2007). These are difficult features to predict without a fine near-surface grid and an accurate turbulence model, however, and thus we have not resorted to any much more approximate techniques in order to account for these effects.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…In addition, the radar studies of de Wit et al (2017) suggest that the large eastward GW momentum flux observed above the stratospheric jet is likely due to secondary waves resulting from MW breaking over the southern Andes. DEEPWAVE airborne observations also provided evidence of trailing waves refracting into the polar vortex in the stratosphere (Jiang et al 2019). Finally, ground-based measurements at the Andes Lidar Observatory at 308S and during DEEPWAVE enabled identification of the instability dynamics accounting for MW breaking in the MLT in two events (Hecht et al 2018;Fritts et al 2019a).…”
Section: Introductionmentioning
confidence: 95%
“…DEEPWAVE was also the first comprehensive airborne mission studying GW dynamics up to the mesopause (∼100 km). To mention just a few outstanding results, DEEPWAVE provided insight into the relation between tropospheric forcing and GW activity in the middle atmosphere (Fritts et al 2016(Fritts et al , 2018Kaifler et al 2015;Bramberger et al 2017;Portele et al 2018), the horizontal propagation of OGW into the polar night jet (Ehard et al 2017), secondary wave generation in regions of strong MW breaking (Bossert et al 2017), the effect of the background atmosphere on GW propagation also in the absence of critical level filtering (Kruse et al 2016), the relative contribution of various parts of the GW spectrum to momentum fluxes (Smith et al 2016;Kruse 2017, 2018;Bossert et al 2018), and the general characteristics of both OGWs and NOGWs (Smith et al 2016;Smith and Kruse 2017;Eckermann et al 2016;Pautet et al 2016Pautet et al , 2019Jiang et al 2019). In the following Section 2, we describe the research aircraft and its instruments dedicated to the measurements of GW properties, along with the ground based measurements in the region.…”
Section: Introduction and Scientific Motivationmentioning
confidence: 99%